Design of a fatigue test bench in rotary flexion to evaluate the behavior to cyclical loads - Araque de los Rios, Oscar Javier; Quintana Avila, Santiago (Scientia et Technica, 2018)
The development of this article shows the process of design, construction and start-up of a fatigue machine in rotary flexion. Fatigue is a subject of considerable relevance and requires adequate equipment for its study, therefore it is sought to contribute to educational and research growth through the development of a functional fatigue machine and where a variety of materials can be studied. The main results were the development of a machine that can carry out a totally inverted stress of 977 Mpa, therefore it can arrive to study steels of high resistance. This machine follows the standards of the normative ASTM E-466 regarding the dimensions of the test specimen. The design of the machine is divided into 3 systems, mechanical system, electrical system and electronic system. When joining these systems obtained a functional and autonomous machine where can make serious and reliable investigations.